Caesarean study at the Naval Medical Center in the last five years - Maradiegue Méndez, Eduardo (2015)
464 caesarean operations between the years 1968 to 1972 with an incidence of 12.27 percent were reviewed. Studies on the age, parity, indications, anesthetic, types of Casarea and complications occurred in these patients is made. The most common indications were iteratively (36.8%) cesarean, cephalo pelvic disproportion (18.3%) and fetal suffering (12%). Unlike previous cesarean it was found in four patients. In three patients cesarean hysterectomy was performed. The post-operative mobility was 16.1%.